On a Maximal Number of Period Annuli - Yelena Kozmina; Felix Sadyrbaev (Abstract and Applied Analysis)
We consider equation x′′+g(x)=0, where g(x) is a polynomial, allowing the equation to have multiple period annuli. We detect the maximal number of possible period annuli for polynomials of odd degree and show how the respective optimal polynomials can be constructed.